Pengaruh Dosis KNO3 dan Waktu Aplikasi terhadap Pertumbuhan dan Produksi Cabai Rawit Domba (Capsicum frutescens L) Di Media Polybag - Mesti; Nurlianti Pertiwi; Prihanani; Farida Aryani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
The research was conducted in Kandang Limun sub-district, Muara Bangkahulu district, Bengkulu city from December 2024 to March 2025. The aim of the research was to determine the effect of the dose and time of KNO3 application and its interaction on the growth and production of Capsicum frutescens L. The research used a factorial Completely Randomized Block Design (CRBD) with a dose of KNO3 (K) with a factor level of K1 = 0 g/plant. K2 = 6 g/plant. K3 = 12 g/plant. Factor 2 is the time of application (W) with the level: W1 = 0 WAP, W2 = 3 WAP. W3 = 6 WAP. The study's results concluded that the dose and timing of KNO3 fertilizer application, as well as their interaction, did not significantly affect the growth variables of chili plants. The time of KNO3 fertilizer application showed a significant effect on fruit length variables. The best fruit length was produced by the 6 WAP fertilizer application treatment (3.11 cm) compared to the 3 WAP treatment (2.89 cm) and the fertilization time at the start of planting 0 WAP (0.56 cm).